Association between psychosocial factors and periodontitis: a case–control study - G. D. C. Castro (Blackwell Synergy, 2006)
Objective: This case-control study investigated the association between life events, anxiety, and depression with periodontitis. Methodology: The study counted with 165 individuals, both sexes, 35–60 years of age. Case group included 96 individuals suffering from periodontal disease; and in control group 69 subjects with no history of periodontitis. Clinical examinations were performed by a single examiner. Psychological assessment included four inventories: Life Events Scale, Beck Anxiety Inventory, State-Trait Anxiety Inventory and Beck Depression Inventory. Bivariate and multivariate logistic regression analyses were performed to compare cases and controls. Results: Mean probing depth and clinical attachment level were 3.44 0.80 and 4.01 1.61 in the case group and 1.96 0.19 and 0.95 0.50 in the control group, respectively (po0.05). Positive association of periodontitis with age (odds ratio (OR)51.15 95% confidence interval (CI): 1.06–1.24), male gender (OR52.71, CI: 1.13–6.49), smoking (OR56.05, CI: 1.67–21.94) and educational level (OR56.49, CI: 1.14–36.95) was confirmed. Bivariate analysis did not demonstrate significant mean differences in life events, anxiety symptoms, trait or state of anxiety, or depression symptoms between cases and controls. Multivariate logistic regression, controlling for confounding factors, demonstrated no significant association between psychosocial factors and periodontal disease. Conclusions: Within the limits of this study it is possible to conclude that there was no significant association between periodontitis and the psychosocial factors analysed.